Effects of Trazodone on Sleep Quality and Cognitive Function in Arteriosclerotic Cerebral Small Vessel Disease Comorbid With Chronic Insomnia - Wang, Jihui; Liu, Sanxin; Zhao, Chongbang; Han, Hongying; Chen, Xiaodong; Tao, Jiong; Lu, Zhengqi (Frontiers in Psychiatry, 2020)
Background: Chronic insomnia is common in patients with arteriosclerotic cerebral small vessel disease (CSVD) and aggravates the cognitive impairment of CSVD. Low dose trazodone is effective in treating insomnia, but it is not clear whether it could improve cognitive function of CSVD along with the relief of insomnia. The aim of this study was to investigate the effects of trazodone on sleep quality and cognitive function in CSVD comorbid with chronic insomnia. Methods: A randomized, double-blind, placebo-controlled clinical trial was conducted. A group of 40 patients experiencing arteriosclerotic CSVD and insomnia was recruited from outpatient clinics. Participants were randomized individually to either trazodone (study group) or to placebo (control group) for 4 weeks. The primary outcome was cognitive function measured by Montreal Cognitive Assessment scale (MoCA). Secondary outcomes included sleep parameters measured by polysomnography (PSG) and Pittsburgh sleep quality index. Results: The trazodone produced significently better improvement in the ability of concentration and recall measured by MoCA, as while as PSG parameters such as sleep efficiency, N3 sleep radio and sleep continuity than placebo. Conclusions: Low dose of trazodone seems acceptable and effective in reducing insomnia severity and cognitive impairment in this small clinically-derived population. Given the high prevalence of insomnia in CSVD patients, our data are supportive of the use of low-dose trazodone as an effective alternative to treat insomnia and cognitive impairment in CSVD.